2011
DOI: 10.1111/j.1099-1123.2011.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative PCAOB Inspections of Triennially Inspected Auditors and Involuntary and Voluntary Client Losses

Abstract: In 2004, the Public Company Accounting Oversight Board (PCAOB) began inspecting registered accounting firms performing audits of US publicly-traded companies. We examine triennially inspected auditors' involuntary and voluntary client losses in the period following receipt of a deficient PCAOB report. We find deficiency reports are associated with triennially inspected auditors being involuntarily dismissed by their clients, and companies dismissing triennially inspected auditors are more likely to hire trienn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 19 publications
2
47
1
Order By: Relevance
“…The underlying assumption of studies using the frequency of going-concern opinions being indicative of audit quality DeFond & Lennox, 2011;) is that that low-quality audit firms are more likely to yield to the pressure of their client, and therefore issue fewer going-concern opinions. 8 The result was supported by Daugherty et al (2011), who found that deficiency reports caused involuntary and voluntary client losses. The figures show that low-quality audit firms voluntarily resigned from their clients because the costs associated with regulatory compliance outweighed the benefits of auditing publicly traded companies.…”
Section: Effect Of Pcaob Inspections On Audit Qualitysupporting
confidence: 72%
See 4 more Smart Citations
“…The underlying assumption of studies using the frequency of going-concern opinions being indicative of audit quality DeFond & Lennox, 2011;) is that that low-quality audit firms are more likely to yield to the pressure of their client, and therefore issue fewer going-concern opinions. 8 The result was supported by Daugherty et al (2011), who found that deficiency reports caused involuntary and voluntary client losses. The figures show that low-quality audit firms voluntarily resigned from their clients because the costs associated with regulatory compliance outweighed the benefits of auditing publicly traded companies.…”
Section: Effect Of Pcaob Inspections On Audit Qualitysupporting
confidence: 72%
“…However, the findings of several other studies show that PCAOB outcomes are recognized for financial decision-making by the financial markets Daugherty et al, 2011;Offermanns & Peek, 2011;Robertson & Houston, 2010, p. 20). Daugherty et al (2011) pointed out that deficiency reports were positively associated with dismissal of audit firms by their clients.…”
Section: Recognition Of Pcaob Inspections For Decision-makingmentioning
confidence: 82%
See 3 more Smart Citations